Intravitreal ranibizumab and bevacizumab therapy for choroidal neovascularization in age-related macular degeneration with extensive pre-existing geographic atrophy - Amaro,Miguel Hage (2012)
PURPOSE: To report the response of choroidal neovascularization to intravitreal ranibizumab or bevacizumab treatment in the setting of age-related macular degeneration with extensive pre-existing geographic atrophy of the retinal pigment epithelium. METHODS: This is a retrospective case series of 11 eyes in ten consecutive patients retrieved from a photographic database. The patients were treated with ranibizumab or bevacizumab for neovascular age-related macular degeneration with pre-existing geographic atrophy. Patients were included if they had geographic atrophy at or adjacent to the foveal center of at least 1 disc area in size that was present before the development of choroidal neovascularization. The best corrected visual acuity and optical coherence tomography analysis of the central macular thickness were recorded for each visit. Serial injections of ranibizumab or bevacizumab were administered until there was complete resolution of subretinal fluid on optical coherence tomography. Data over the entire follow-up period were analyzed for overall visual and optical coherence tomography changes. RESULTS: The patients received an average of 7 ± 3 intravitreal injections over the treatment period. Seven of 11 eyes had reduced retinal thickening on optical coherence tomography. On average, the central macular thickness was reduced by 72 ± 115 µm. Six of these 7 eyes had improvement of one or more lines of vision and one had no change. The average acuity change for all patients was -0.04 ± 0.46 logMAR units, which corresponded to a gain of 0.2 ± 4.4 lines of Snellen acuity. The treatment resulted in a good anatomic response with resolution of the subretinal fluid and overall stable visual acuity. CONCLUSIONS: The results of this case series suggest that the use of an intravitreal anti-vascular endothelial growth factor (VEGF) agent (ranibizumab or bevacizumab) for choroidal neovascularization in age-related macular degeneration with pre-existing geographic atrophy is effective. Our results are not as striking as published results from large-scale trials of anti-vascular endothelial growth factor therapy for subfoveal choroidal neovascularization, presumably due to the limitation in the baseline visual acuity caused by the underlying geographic atrophy. The favorable anatomic response with the resolution of subretinal fluid and stable acuity were consistent with other ranibizumab and bevacizumab studies.